INFLUÊNCIA DA COMUNICAÇÃO POLÍTICA NO SISTEMA DE VOTAÇÃO ELETRÔNICO BRASILEIRO - Macedo, Roberto Gondo (2011)
The speed of information and knowledge in contemporary society introduced a constant search for improved information processes, in order to ensure more rapid processing and results. In the world public, the requirements go a similar way, under the gaze of the citizen voter, so the research proposal is to provide a panorama of Brazilian electronic voting system, specifically the electronic ballot box and carried the project from conception of the ides 90´s to the present time, pointing to a scientific look at the communication actions of the Supreme Electoral Tribunal, to promote campaigns to raise awareness of the computerized system of voting by electors, supposedly faster and more efficient. The research used for descriptive purposes multiple views of a communication: through the body maintainer, politicians directly involved in competitive elections and political consultants, working backstage in the strategies of electoral campaigns. This diversity of views and positions regarding the credibility of the system aims to provide a character study of macro understanding of the impacts of a computerized system in a democratic environment.